Differential MicroRNA Expression Levels in Cutaneous Acute Graft-Versus-Host Disease - Atarod, Sadaf; Norden, Jean; Bibby, Louis A.; Janin, Anne; Ratajczak, Philippe; Lendrem, Clare; Pearce, Kim F.; Wang, Xiao-Nong; O’Reilly, Steven; Van Laar, Jacob M.; Collin, Matthew; Dickinson, Anne M.; et al. (Frontiers in Immunology, 2018)
Allogeneic haematopoietic stem cell transplantation (allo-HSCT) is a curative treatment for numerous haematological malignancies. However, acute graft-versus-host disease (aGvHD) is a major complication affecting 40-70% of all transplant patients, whereby the earliest and most frequent presentation is in the skin. MicroRNAs play a role in varied biological process and have been reported as potential biomarkers for aGvHD. More recently, microRNAs have received added attention as circulatory biomarkers that can be detected in biofluids. In the present study we performed global microRNA expression profiling using a discovery cohort of diagnostic cutaneous aGvHD biopsies (n=5, stage 1-3) and healthy volunteers (n=4), in order to identify a signature list of microRNAs that could be used as diagnostic biomarkers for cutaneous aGvHD. Candidate microRNAs (n=8) were then further investigated in a validation cohort of post-HSCT skin biopsies (n=17) for their association with aGvHD. Expression of miR-34a-5p (p<0.001), miR-34a-3p (p=0.013), miR-503-5p (p=0.021) and let-7c-5p (p=0.037) was elevated in cutaneous aGvHD and significantly associated with survival outcome (miR-34a-3p ROC AUC=0.93, p=0.003, Log Rank p=0.004; miR-503-5p ROC AUC=0.83 p=0.021, Log Rank p=0.003). There was no association with relapse. A statistical interaction between miR-34a-3p and miR-503-5p (p=0.016) was diagnostic for aGvHD. Expression levels of the miR-34a-5p protein target p53 were assessed in the epidermis of the skin, and an inverse correlation was identified (r2=0.44, p=0.039). Expression of the validated candidate microRNAs was also assessed at day 28 post-HSCT in the sera of transplant recipients, in order to investigate their potential as circulatory microRNA biomarkers. Expression of miR-503-5p (p=0.001), miR-34a-5p (p=0.005) and miR-34a-3p (p=0.004) were significantly elevated in the sera of patients who developed aGvHD vs. no-aGvHD (n=30) and miR-503-5p was associated with overall survival (ROC AUC=0.80, p=0.04, Log Rank p=0.041). In conclusion, this investigation reports that microRNA expression levels in clinical skin biopsies, obtained at the time of cutaneous aGvHD onset, show potential as diagnostic biomarkers for aGvHD and as predictive biomarkers for overall survival. Additionally, the same microRNAs can be detected in the circulation and show predictive association with post-HSCT outcomes.